Electro-thermal dynamics in superconducting generators: An In-Depth investigation of AC losses and cooling techniques for a 10 MW rotor coil system - Erciyas, A.; Yildiz, S.; Inanir, F. (ELSEVIER, 2024)
In the pursuit of optimizing superconducting generator systems, a comprehensive understanding of their electrothermal behaviors is crucial. This study builds upon previous research on an 8-pole, 10 MW superconducting generator by Inanir et al. (2022, Journal of Superconductivity and Novel Magnetism, 35(11), 3189) and focuses on an in-depth electro-thermal analysis of the rotor coil system. The emphasis is on assessing the AC losses experienced during transitory current changes. By simultaneously solving Ampere's equation and the heat conduction equation under specific boundary conditions, the research provides a detailed insight into the interaction between electrical and thermal dynamics within the rotor coils. The paper highlights the importance of temperature dynamics in various cooling and current conditions. The results demonstrate that achieving an optimal balance in cooling, particularly with the use of liquid nitrogen, is critical for efficient operation. This study not only advances the understanding of superconducting generators but also highlights potential strategies for improving their reliability and efficiency.
Keywords: Superconducting generators; AC Loss; Cooling of Coil system; Physics